Continuous Piperacillin-Tazobactam Infusion Improves Clinical Outcomes in Critically Ill Patients with Sepsis: A Retrospective, Single-Centre Study - Dong-gon Hyun; Jarim Seo; Su Yeon Lee; Jee Hwan Ahn; Sang-Bum Hong; Chae-Man Lim; Younsuck Koh; Jin Won Huh (MDPI AG, 2022)
Continuous infusion of beta-lactam antibiotics has emerged as an alternative for the treatment of sepsis because of the favourable pharmacokinetics of continuous infusion. This study aimed to evaluate the survival benefits of continuous vs. intermittent infusion of piperacillin-tazobactam in critically ill patients with sepsis. We retrospectively conducted a single-centre study of continuous infusion vs. intermittent infusion of piperacillin-tazobactam for adult patients who met the Sepsis-3 criteria and were treated at a medical ICU within 48 h after hospitalisation between 1 May 2018 and 30 April 2020. The primary outcome was mortality at 28 days. A total of 157 patients (47 in the continuous group and 110 in the intermittent group) met the inclusion criteria for evaluation. The 28-day mortality rates were 12.8% in the continuous group and 27.3% in the intermittent group (p = 0.07). However, after adjustment for potential covariables, patients in the continuous group (12.8%) showed significantly lower mortality at 28 days than those in the intermittent group (27.3%; adjusted hazard ratio (HR), 0.31; 95% confidence interval (CI), 0.13-0.79; p = 0.013). In sepsis patients, continuous infusion of piperacillin-tazobactam may confer a benefit regarding the avoidance of mortality at 28 days compared with intermittent infusion.